(untitled) (Third Sector Social Economic Review, 2022)
The aim of this study is to search the effect of perception of employee’s overqualification on job performance and its mediating role of phsychological ownership. For this purpose relational survey model is used. Data is collected from 424 personnel working in different departments of Ministry of Trade with different titles. Personnel form, Scale of Perceieved Overqualification, Psychological Ownership and Job Performance are used. Frequancy, Correlation and Reliabilty Analaysis and Structural Equilance Model is used in order to analyse the relation of direct and indirect variables. It is found that the measuring tools used in the search are reliable. According to the results of this search, perceived overqualification has a negative effect on contextual performance and tax performance those are dimensions of job performance. Psychological ownership has a positive effect on contextual perfomance and tax performance. Phsychological ownership has a mediating role on the effect of perceieved overqualification on job performance. Goodness of fit measures are acceptable. As a result, perceived overqualification has a negative effect on job performance. Besides the negative effect of perceived over qualification effects job performance negatively.